2015
DOI: 10.1111/jsr.12359
|View full text |Cite
|
Sign up to set email alerts
|

Do repeated rumble strip hits improve driver alertness?

Abstract: SummaryDriving while sleepy is associated with increased crash risk. Rumble strips are designed to alert a sleepy or inattentive driver when they deviate outside their driving lane. The current study sought to examine the effects of repeated rumble strip hits on levels of physiological and subjective sleepiness as well as simulated driving performance. In total, 36 regular shift workers drove a high-fidelity moving base simulator on a simulated road with rumble strips installed at the shoulder and centre line … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 24 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…The KSS has been validated against performance tasks and EEG variables in laboratory settings and it is related to driving performance in simulator and real driving [1], [50], [51]. In this study KSS = 7 was selected as threshold for classification as studies have demonstrated that KSS level 8 and 9 are clearly associated with driving performance impairment and physiological changes [1], [52], [53]. Using KSS will not identify exact occurrence of microsleep events, which causes deterioration in driving performance [54], and current 5-min HRV processing window may not be suitable to precisely locate microsleep events that usually have a duration of few seconds.…”
Section: Discussionmentioning
confidence: 99%
“…The KSS has been validated against performance tasks and EEG variables in laboratory settings and it is related to driving performance in simulator and real driving [1], [50], [51]. In this study KSS = 7 was selected as threshold for classification as studies have demonstrated that KSS level 8 and 9 are clearly associated with driving performance impairment and physiological changes [1], [52], [53]. Using KSS will not identify exact occurrence of microsleep events, which causes deterioration in driving performance [54], and current 5-min HRV processing window may not be suitable to precisely locate microsleep events that usually have a duration of few seconds.…”
Section: Discussionmentioning
confidence: 99%
“…This procedure allowed for clear separation of the two classification states. Several studies show KSS values of 8 or more clearly demonstrate sleepiness-related impairment (Ingre et al, 2006;Watling et al, 2016) and, importantly, are predictive of a greater likelihood of on-road sleep-related crashes (Åkerstedt et al, 2008). Though, it should be noted that KSS ratings, like any subjective/self-report data, are subject to bias and can be influenced by the context (monotonous settings, light levels, social interaction) when ratings are obtained (Åkerstedt et al, 2014).…”
Section: Issues Of Consistencymentioning
confidence: 99%
“…Alternative, proactive means of preventing fatigue-related errors may involve "smart" or dynamic adaptations to changes in performance or other signs of fatigue (e.g., through systems that monitor the physiological status of an individual through heart rate variability, eye gaze, or other metrics and modify workload or other task variables accordingly) [15]. However, the effectiveness of such safety features may be diminished when individuals are sleep-deprived [16][17][18].…”
Section: Introductionmentioning
confidence: 99%